Hydrogen – microstructure – mechanical properties interactions in super duplex stainless steel components - Craidy, Pedro da Silva (2018)
The increasing demand for energy requires the exploration of oil and gas at deeper water locations and on more severe conditions. These production systems have demanded the use of forged equipments made of higher strength steel grades, such as austenitic-ferritic (duplex) stainless steels. These components are more prone to exhibit loss of ductility and general mechanical performance caused by hydrogen generated e.g. by cathodic protection. Duplex stainless stainless steels components present a vast history of hydrogen damage at low temperatures, due to hydrogen derived from various sources. Even being this kind of damage fairly recurring, various related information remains to be elucidated, due to the complex interaction of hydrogen with the microstructure and localized character of hydrogen generation and transportation in the material. The present work aims to improve the physical understanding of the interaction between hydrogen and the microstructure as well as the effects of different hydrogen charging procedures on the mechanical properties of forged components made of the super duplex stainless steel grade UNS S32750. The development of such understanding involves the evaluation of the effects of hydrogen on the mechanical properties of the material through tensile tests in different hydrogen-rich environments. Based on results of slow-strain rate tensile tests, a quantitative relationship between embrittlement caused by gas hydrogen and cathodic charging is proposed, and possible effects of dislocation-assisted hydrogen transportation and embrittlement are discussed. Quantitative and qualitative descriptions of the hydrogen transportation, including analysis of the effects of different microstructures and diffusion paths, and of its position in the lattice and in the microstructure (hydrogen segregation to traps) are proposed.